ANALYSIS OF MODERN SPREADING EQUIPMENT APPLIED IN THE SEWING INDUSTRY - SLAVINSKA, Alla; SYROTENKO, Oksana (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The productivity and efficiency of cutting and sewing production is impossible without the use of the latest and most reliable equipment. Ensuring their smooth operation requires the use of high-quality main and supporting equipment. Due to factors such as complex typesetting of skilled workers, high labor costs and the complexity of clothing production, layout and cutting play a critical role. It is the foundation and key that cannot be ignored in the sewing industry. The spreading and cutting department has special importance in garment manufacturing, it is not possible to make a garment in large quantities without a cutting room. The article considers the list of basic and additional spreading equipment for the cutting room. The most common manufacturer brands and companies supplying this equipment on the Ukrainian market are analyzed.The specified descriptive characteristics of the features of the spreading equipment are given and their latest technological solutions are indicated. The comparative characteristics of the technical parameters of the equipment of various models and manufacturers are given. The cost characteristics of equipment of different price groups (low, medium and high) are presented. The most cost-effective types of equipment are recommended for enterprises of different capacities and types of activity. The expediency of ensuring the consistency of spreading and cutting equipment of the same manufacturer brand at the same enterprise is indicated. The conducted analysis indicates a wide market of modern spreading equipment for cutting department of sewing enterprises, which allows you to freely choose the desired option. The primary factor in this case is the manufacturer's brand and equipment model, and its cost is an equally important factor. They must provide the desired capacity of the enterprise and should be profitable.
Keywords: cutting room; cutting tables; cutting lines; unwinders for rolls; spreading complexes